Dietary fibre and the gut–brain axis: microbiota-dependent and independent mechanisms of action - Danique La Torre; Kristin Verbeke; Boushra Dalile (Gut Microbiome, 2021)
Dietary fibre is an umbrella term comprising various types of carbohydrate polymers that cannot be digested nor absorbed by the human small intestine. Consumption of dietary fibre is linked to beneficial effects on cognitive and affective processes, although not all fibres produce the same effects. Fibres that increase short-chain fatty acid (SCFA) production following modulation of the gut microbiota are thought to be the most potent fibres to induce effects on cognitive and affective processes. SCFAs can exert their effects by improving central, peripheral and systemic immunity, lowering hypertension and enhancing intestinal barrier integrity. Here, we propose additional mechanisms by which dietary fibres may contribute to improvements in affective and cognitive processes. Fibre-induced modulation of the gut microbiota may influence affective processes and cognition by increasing brain-derived neurotrophic factor levels. Depending on the physicochemical properties of dietary fibre, additional effects on affect and cognition may occur via non-microbiota-related routes, such as enhancement of the immune system and lowering cholesterol levels and subsequently lowering blood pressure. Mechanistic randomised placebo-controlled trials are needed to establish the effects of dietary fibre consumption and the magnitude of explained variance in affect and cognition when incorporating measurements of microbiota-dependent and microbiota-independent mechanisms in humans.